2012
DOI: 10.5812/asjsm.34721
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Combined High-Intensity Plyometric and Speed Training Program on the Running and Jumping Ability of Male Handball Players

Abstract: Purpose: The aim of this study was to investigate the effect of a combined program including sprint repetitions and drop jump training in the same session on male handball players.Methods: Twenty-two male handball players aged more than 20 years were assigned into 2 groups: experimental group (n=11) and control group (n=11). Selection was based on variables "axis" and "lines", goalkeepers were not included. The experimental group was subjected to 2 testing periods (test

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
30
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 23 publications
7
30
0
3
Order By: Relevance
“…Combined training is considered to be one of the important parts of the training programmes used by fitness coaches to develop both muscle strength and power [16]. In this context and in agreement with the present study findings, Coffey and Hawley [17] stated that this exercise mode positively influenced the training adaptations in skeletal muscle.…”
Section: Discussionsupporting
confidence: 90%
“…Combined training is considered to be one of the important parts of the training programmes used by fitness coaches to develop both muscle strength and power [16]. In this context and in agreement with the present study findings, Coffey and Hawley [17] stated that this exercise mode positively influenced the training adaptations in skeletal muscle.…”
Section: Discussionsupporting
confidence: 90%
“…The exercises selected contained many powerful multidirectional movements, which may had an impact on the capacity to change direction faster. Again, although this improvement could be positive for the tennis players' performance, previous research showed higher gains in jump height, with 4.7-15% improvement after explosive power training (i.e., plyometric training) (10,16). This supports the idea that adaptations (e.g., mechanical and physiological) and associated changes in performance after a training intervention are to a certain extent training specific, with the energy system, the muscle group, the contraction force, or the movement patterns engaged, each playing a role in determining the final adaptations (27,43).…”
Section: Discussionmentioning
confidence: 70%
“…Based on previous research, conducting ExpS (9,10,30,37) or RS (10,19,20) alone, one can expect greater effects of ExpS or RS training programs alone than a combined program. These improvements seem to be clearly related to the concept of training specificity (43), highlighting that in complex sports as tennis, fitness qualities (i.e., jumping ability and RSA) might need to be developed independently, and therefore, athletes need specific training sessions, which should be part of the training program.…”
Section: Discussionmentioning
confidence: 99%
“…It has also indicated that certain physical features are related to high-level handball performance. Strength, jumping abilities and maximal running speed have an impact on handball performance [15,16,17]. As talency of vertical jump, provides a great advantage while throwing or blocking in defence is one of the most important basic features.…”
mentioning
confidence: 99%